2011
DOI: 10.1021/ml200017d
|View full text |Cite
|
Sign up to set email alerts
|

Prodrugs of a CXC Chemokine-12 (CXCL12) Neutraligand Prevent Inflammatory Reactions in an Asthma Model in Vivo

Abstract: Chalcone 4 (compound 1) is a small molecule that neutralizes the CXC chemokine CXCL12 and prevents it from acting on the CXCR4 and CXCR7 receptors. To overcome its poor solubility in aqueous buffers, we designed highly soluble analogues of compound 1, phosphate, L-seryl, and sulfate, all inactive by themselves on CXCL12 but when cleaved in vivo into 1, highly active locally at a low dose in a mouse airway hypereosinophilia model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 19 publications
1
39
0
Order By: Relevance
“…The compound is a prodrug; after in vivo cleavage of the phosphate group, it converts into the active chalcone 4 molecule that selectively binds CXCL12 and neutralizes its function. 24 Chalcone 4 was shown to prevent induction of CXCR4 signaling and CXCL12-mediated CXCR4 internalization in vitro. 23 To investigate whether elevated levels of circulating CXCL12 were required for mobilization of leukocytes and HPCs by AMD3100, we administered C4P IV (1.5 mmol/kg) to neutralize CXCL12 in the peripheral circulation.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The compound is a prodrug; after in vivo cleavage of the phosphate group, it converts into the active chalcone 4 molecule that selectively binds CXCL12 and neutralizes its function. 24 Chalcone 4 was shown to prevent induction of CXCR4 signaling and CXCL12-mediated CXCR4 internalization in vitro. 23 To investigate whether elevated levels of circulating CXCL12 were required for mobilization of leukocytes and HPCs by AMD3100, we administered C4P IV (1.5 mmol/kg) to neutralize CXCL12 in the peripheral circulation.…”
Section: Resultsmentioning
confidence: 98%
“…21 As with AMD3100, preliminary studies investigating the anti-HIV activity of KRH3955 showed that a single dose of this drug elevated leukocyte counts in peripheral blood. 22 Here, we have made use of a specific CXCL12 neutraligand, chalcone 4-phosphate, 23,24 to address the question of whether an elevation of CXCL12 in the plasma is required for mobilization of HPCs and MPCs by these distinct CXCR4 antagonists.…”
Section: Introductionmentioning
confidence: 99%
“…AMD3100 (or plerixafor) was from Sigma-Aldrich. Chalcone 4 was prepared as described in Gasparik et al 16 and in supplemental Methods. Descriptions of the culture and transfection are provided in supplemental Methods.…”
Section: Reagents Cell Culture and Transfectionmentioning
confidence: 99%
“…Chalcone 4 was identified as an inhibitor of the interaction between CXCR4 or CXCR7 and their ligand CXCL12 [6, 14] through binding to the chemokine in a neutralizing-like manner rather than on its receptors [15]. Chalcone 4 was therefore called a neutraligand.…”
Section: Introductionmentioning
confidence: 99%
“…Chalcone 4 was therefore called a neutraligand. Administered intranasally, chalcone 4 decreased the recruitment of inflammatory cells, in particular eosinophils, in a mouse model of allergic eosinophilic airway inflammation [6, 14]. Furthermore, chalcone 4 derivatives, modified as highly soluble prodrugs, attenuated at very low doses the inflammatory reaction in an allergic airway hypereosinophilia model [14].…”
Section: Introductionmentioning
confidence: 99%